The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1128/spectrum.02073-22
|View full text |Cite
|
Sign up to set email alerts
|

Plant Signals Anticipate the Induction of the Type III Secretion System in Pseudomonas syringae pv. actinidiae , Facilitating Efficient Temperature-Dependent Effector Translocation

Abstract: Plant diseases—their occurrence and severity—result from the impact of three factors: the host, the pathogen, and the environmental conditions, interconnected in the disease triangle. Time was further included as a fourth factor accounting for plant disease, leading to a more realistic three-dimensional disease pyramid to represent the evolution of disease over time.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
3
3
0
Order By: Relevance
“…Regarding P. syringae pv. actinidiae , our results confirmed a low-temperature dependency for T3SS efficiency (Puttilli et al ., 2022), which is entirely in line with the environmental conditions – in late winter or early spring – under which P. syringae pv. actinidiae is reported to cause disease or damage in the kiwifruit orchards (Kim et al ., 2017; Donati et al ., 2020).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding P. syringae pv. actinidiae , our results confirmed a low-temperature dependency for T3SS efficiency (Puttilli et al ., 2022), which is entirely in line with the environmental conditions – in late winter or early spring – under which P. syringae pv. actinidiae is reported to cause disease or damage in the kiwifruit orchards (Kim et al ., 2017; Donati et al ., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…glycinea could be involved in the regulation of T3SS-related gene expression in response to temperature (Ullrich et al ., 1995). Alternatively, if evidence hints that gene expression is not directly modified by temperature (Puttilli et al ., 2022), thermoregulation might act later in the transcription/translation chain, during T3SS assembly, or on translocation efficiency. In addition, the study of potential differences in membrane fluidity between strains is promising.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, our results showed that 6 out of 10 isolates exhibited signi cant upregulation of T3SS expression in the presence of sugar beet extract, highlighting the speci city of this system to the sugar beet host and suggesting a specialised mechanism for the delivery of T3Es to this particular plant species. This observation is consistent with the existing literature on pathogens in which host-speci c signalling triggers T3SS expression (Puttilli et al, 2022). Contrary to expectations, the addition of sugar beet extract led to a down-regulation of T3SS expression in certain isolates, including the aforementioned P. corrugata MRh80.…”
Section: Discussionsupporting
confidence: 91%